Uma análise dos leilões de partilha de produção do pré-sal através de simulação computacional - Almeida, André Silva (2013)
This work considers the application of computer simulation as a method of deepening the study of mechanisms for auctions applied in the allocation of oil exploitation rights in the pre-salt layer. The pre-salt layer is located in the Brazilian coast and presents a large potential in terms of barrel of oil equivalent. Based on an experimental data, the bid function was estimated as an exponential function and applied at the participants created computationally. Considering all features and parameters of the experiments, the simulation allows to reproduce the auction model without incurring implementation costs on new auction sessions with real participants. The auction models studied were the rst-price sealed-bid auction and the second-price sealed-bid auction. The results show that the rst-price sealed-bid auctions are less risky than the second-price sealed-bid auctions; the Revenue Equivalence Principle is valid on symmetric auctions; asymmetric auctions present lower e ciency compared to the rst-price auction; the second-price auction presents a tra- deo between e ciency and government revenue; and considering participant learning, were not observed signi cant changes on the statistics analyzed as the participants become more experienced.